Air Pollution and Health Hazards: A Narrative Review from the Bangladesh Perspective - Islam, Samprity; Tarik, Imtiaz; Islam, Mohammad Khairul; Kabir, Mohammed Humayun; Sajib, Shaikh Mohammed; Bhadra, Abhisehek (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Air pollution poses a severe health hazard in Bangladesh, contributing to approximately 173,500 deaths in 2019. This review examines the pervasive impact of PM2.5 and PM10 pollutants emanating from sources like brick kilns, vehicles, and biomass burning, surpassing safe thresholds. These pollutants are linked to widespread respiratory diseases, cardiovascular complications, and elevated mortality rates among the population. Despite regulatory efforts, persistent challenges underscore the urgent need for cleaner technologies, sustainable urban planning, and heightened public awareness campaigns. Effective global and national strategies are crucial to mitigate these health risks and foster sustainable development in Bangladesh and globally. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):101-106